Positive and Negative Impacts of Selenium on Human Health and Phytotoxicity - Tripathi G.; Srivastava D.K.; Mishra V. (My University, 2025)
Selenium (Se) as selenoproteins has multiple unrelated characteristics, like anti-inflammatory and antioxidants related to the secretion of thyroid hormone. In the past few years, the research into disease associated with the selenoprotein gene has paid attention to the role of selenoproteins in health. A low concentration of selenium has a high risk of poor immunity, cognitive decline, and mortality. Higher supplementation of selenium has antiviral effects, is required to minimize the danger of autoimmune thyroid infection and is effective in male and female proliferation. Research investigations have indicated some benefits of higher selenium concentration as regards the risk associated with colorectal, lung, bladder, prostate cancers, etc. Therefore, the only thing to be considered regarding the intake of selenium is its optimal concentration requirement in the body. Plants are the major source of Se in the diet, but the necessity of Se for plants is debatable. Low Se doses have protected plants from a variety of abiotic stresses. Sulfur transporters that are present inside the plasma membrane of root take up Se inside the plants. Protein structure, oxidative stress, and function distortion induced by Se are the major causes of high dose toxicity of Se in plants. For overcoming the Se toxicity and Se deficiency among the population, plants can play an effective role. Thus, a detailed study of mechanism and metabolism of Se inside the plant is important for applications like biofortification and phytoremediation. © 2021 John Wiley & Sons Ltd. All rights reserved.